算法嵌入政府治理:逻辑、风险与规制. - 周晓丽; 姬晓暄 (Journal of Xi'an Jiaotong University (Social Sciences), 2024)
In recent years, with the rapid development of modern information technology, intelligent algorithms have been deeply embedded in all aspects of social life, which not only promotes the continuous development of human economy and society to intelligence, but also promotes the overall pattern of society to intelligence, providing technical guidance for the efficient and orderly operation of national governance and becoming an important driving force for the modernization of national governance level and governance capacity. In this context, how to promote the algorithm technology to be more effectively embedded in government governance at this stage, how to counter the origin of technology while giving full play to technical benefits, and how to better achieve the goal of maximizing public value become an urgent proposition of the times. In this paper, an analytical framework is built from the three dimensions of "technology-power-rules" to study the embedding of algorithms into government governance. Taking the practice of embedding algorithms into different scenes of government governance as the observation window, the operational logic and value implication of enabling government governance by algorithms are explored, and it is proposed that algorithm technology can promote public decision-making to be more rational, algorithm power can promote governance behavior to be more inclusive, and algorithm rules can promote government governance to be more fair. At the same time, it focuses on the risks and challenges that may be brought by the application of algorithms with technical, power and rule attributes in government governance practice, such as the black box of algorithm technology blocking the identification of public responsibility, the power of algorithm weakening the autonomy of government and people, and the preference of algorithm rules leading to the loss of governance justice. Combined with the government governance practice in China, it is proposed that in order to promote the intelligent algorithm to be more effectively embedded in government governance and better realize the goal of maximizing public benefits, efforts should be made to promote the moderate transparency of algorithm technology to clarify the chain of responsibility, standardize the operation of algorithm power and adhere to the humanistic governance concept. Different from the "negative theory of algorithm" and "positive theory of algorithm" held by the existing research results, this paper recognizes that the algorithm has both positive and negative external benefits to government governance from the two dimensions of efficiency and value, and focuses on how to avoid or reduce the possible risks and challenges of the algorithm to government governance from the three levels of technology, power and rules, and amplify the positive benefits of the algorithm to the governance process, so that the intelligent algorithm can be truly and effectively embedded in government governance, and promote the quality and efficiency of social governance.